Concussions From Youth Football: Results From NEISS Hospitals Over an 11-Year Time Frame, 2002-2012. Issue 7 (27th December 2013) - Jacobson, Nathan A.; Buzas, David; Morawa, Lawrence G.
Background: Youth football programs across the United States represent an at-risk population of approximately 3.5 million athletes for sports-related concussions. The frequency of concussions in this population is not known. Study Design: Descriptive epidemiology study. Methods: Over an 11-year span from January 2002 to December 2012, the authors reviewed the concussions sustained by athletes aged 5 to 13 years while playing football, as evaluated in emergency departments (EDs) in the United States and captured by the National Electronic Injury Surveillance System (NEISS) database of the US Consumer Product Safety Commission. Results: There were 2028 (national estimate, 49, 185) young football players evaluated in NEISS EDs with concussion from 2002 to 2012. There were 1987 (97.9%) males and 41 (2.1%) females, with a mean age of 11.2 years. The total number of concussions reported increased with age and by year. The majority of concussions were treated in the outpatient setting, with 1878 (91.7%) being treated and released. The total number of head-to-head injury mechanisms mirrored the total number of concussions by year, which increased throughout the 11-year span. The total number of players experiencing a loss of consciousness increased throughout the study period but did not match the total number of concussions over the 11-year time period. Fractures occurred in 11 (0.5%) patients, with 2 being severe (1 skull fracture and 1 thoracic compression fracture). Conclusion: Within the 5- to 13-year age range, there were a significant number of young athletes who presented to EDs with concussion as a result of playing organized football. Older children may be at greater risk for sustaining concussions, fractures, and catastrophic injuries while playing football when compared with younger children. Clinical Relevance: Younger children are more susceptible to long-term sequelae from head injuries, and thus, improved monitoring systems for these athletes are needed to assist in monitoring patterns of injury, identifying risk factors, and driving the development of evidence-based prevention programs.